Control of redox homeostasis in tick blood feeding - Sabadin, Gabriela Alves (2019)
Introduction: Ticks are hematophagous ectoparasites that cause significate economical losses. Acaricide application is the main method to tick control. However, it causes environmental contamination and selects resistant ticks. The immunological control represents a suitable method to replace or complement acaricide application. During its life cycle, female ticks ingest large amounts of blood, which contains toxic components able to damage biomolecules. Understanding which molecular mechanisms and proteins are involved in avoid damages caused by blood intake in ticks and other hematophagous arthropods could help to found potential candidate antigens to compose an anti-tick vaccine. Review: Hemoglobin comprises almost 20% of mammalian blood proteins, its hydrolysis during tick digestion increases total free heme that can potentially generate reactive oxygen species (ROS), which easily oxidize lipids, proteins and DNA, modifying they structure and function. Lipids are more susceptible to high ROS levels. It can lead to membrane instability and cell death. Protein modifications caused by ROS can promote the protein loss of function and cell disturbance, however, it can also work as post-translational modifications, acting in cell signaling processes. DNA presents more efficient protective mechanisms against ROS, but damages can lead to double helix rupture. Oxidative stress is defined as a disturbance in the balance between the production and elimination of ROS, in favor of ROS production, leading to a disruption in redox homeostasis and/or molecular damage. Despite the well-recognized heme oxidative power and its already demonstrated cytotoxicity, ticks are able to feed on blood, controlling the redox homeostasis without causing oxidative stress. This occurs because ticks developed physiological adaptations to transport, store, metabolize and secrete toxic components from the diet. The strategies, such as heme compartmentalization in specialized organelles, and heme and iron carrying proteins are shared with most of other hematophagous. Interesting, heme degradation, a mechanism commonly described in hematophagous arthropods, showed to be absent in ticks. Moreover, there is a lack of key enzymes from the heme degradation pathway in tick genomes. As expected, antioxidant enzymes are often involved in homeostasis redox control. They act in a convenient way, eliminating physiological and non-physiological produced ROS. Despite their essential role in non-hematophagous organisms, antioxidant enzymes were associated with blood ingestion during arthropod hematophagous process, demonstrating their role in avoiding oxidative stress caused by blood intake. Catalase showed to be essential to heme detoxification in Rhipicephalus microplus tick, and diverse antioxidant enzymes are up-regulated after blood intake in a variety of hematophagous parasites. If in one hand ROS is responsible to cell damage and oxidative stress, on the other hand, several works revealed the fundamental role of ROS in cell signaling and function, demonstrating the sophisticated regulation that is necessary to redox homeostasis control. Conclusions: In the course of arthropods evolution, blood-feeding life style represent a special strategy to acquire energy and biosynthetic precursors. Together with this advantage, hematophagous organisms needed to develop molecular mechanisms to control toxic components ingested with blood. In this context, several works reviewed here identified the role of proteins and enzymes in the control of free heme released during hematophagy and in redox homeostasis, in order to avoid oxidative stress caused by blood intake. This knowledge represents an important contribution in the search for new candidate targets to develop efficient tick control methods.